Fano resonance Rabi splitting of surface plasmons - Zhiguang Liu (Nature Portfolio, 2017)
Abstract Rabi splitting and Fano resonance are well-known physical phenomena in conventional quantum systems as atoms and quantum dots, arising from strong interaction between two quantum states. In recent years similar features have been observed in various nanophotonic and nanoplasmonic systems. Yet, realization of strong interaction between two or more Fano resonance states has not been accomplished either in quantum or in optical systems. Here we report the observation of Rabi splitting of two strongly coupled surface plasmon Fano resonance states in a three-dimensional plasmonic nanostructure consisting of vertical asymmetric split-ring resonators. The plasmonic system stably supports triple Fano resonance states and double Rabi splittings can occur between lower and upper pairs of the Fano resonance states. The experimental discovery agrees excellently with rigorous numerical simulations, and is well explained by an analytical three-oscillator model. The discovery of Fano resonance Rabi splitting could provide a stimulating insight to explore new fundamental physics in analogous atomic systems and could be used to significantly enhance light-matter interaction for optical sensing and detecting applications.